Waitting roon group: human aging meaning’s - Moreira Jr., Cesar Sandoval; Japur, Marisa (Paidéia (Ribeirão Preto), 2003)
This research question the human aging while universal experience. Using the social construcionism, the waiting room group is understood as a discursive production, having the language as a main point of social practices and focalizing a relational perspective in the producing process of the world meanings. Thinking about this psychological intervention, we have the purpose of describing the meaning production process about the human aging in this context. Ten waiting room groups, recorded and transcribed, were analyzed, what made possible the selection of one of them for extensive analyses. Their analysis show that in this conversation the aging experience like an individual experience is being changed by the speakers as social interaction, pointing to actives positions on healthy life quality aging production. The speakers construct several meanings about aging, talk about themselves in their daily relationships, creating the possibility for new descriptions about themselves as elders in this interactive context.